2013
DOI: 10.1136/annrheumdis-2012-203135
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative effects of neuromuscular exercise prior to hip or knee arthroplasty: a randomised controlled trial

Abstract: ClinicalTrials NCT01003756.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(147 citation statements)
references
References 27 publications
5
139
2
1
Order By: Relevance
“…Before randomization of the first patient, the multiple primary endpoints were changed to one single primary endpoint ('HOOS function'). The rationale for this change was to avoid multiplicity and improve the comparison of intervention effects with a previous high quality RCT using similar endpoint 28,29 . Consequently the sample size calculation used in the study protocol was based on the clinical relevant difference of 'HOOS function' 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Before randomization of the first patient, the multiple primary endpoints were changed to one single primary endpoint ('HOOS function'). The rationale for this change was to avoid multiplicity and improve the comparison of intervention effects with a previous high quality RCT using similar endpoint 28,29 . Consequently the sample size calculation used in the study protocol was based on the clinical relevant difference of 'HOOS function' 29 .…”
Section: Methodsmentioning
confidence: 99%
“…The outcomes specifically depict that knee problems resolve after neuromuscular exercise training for a specified time frame. A randomized controlled trial was conducted by Villadsen et al [31], demonstrating beneficial results of neuromuscular exercises after hip and knee arthroplasty. The trial also mentions that neuromuscular exercises are beneficial for tendons and muscles during strains.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have clearly shown the efficacy and advantages of exercises prior to THA or TKA as well as the numerous positive effects preoperative exercises have on the outcomes of the patient (Huang, Chen & Chou 2011;Matassi et al 2014;Swank et al 2011;Villadsen et al 2014). Preoperative exercises improve the psychological health, social life and quality of life of the patient (Czyżewska et al 2014).…”
Section: Activitymentioning
confidence: 99%
“…Preoperative exercises improve the psychological health, social life and quality of life of the patient (Czyżewska et al 2014). During interviews in studies conducted by Villadsen et al (2014) and Topp et al (2009), participants expressed a lack of interest in preoperative exercises, as their main concern was pain relief, clearly indicating that participants were unaware that preoperative exercises might actually reduce their preoperative and post-operative pain. Our study showed that both the THA and TKA participants' most common preoperative symptom was pain, whereas the majority of the participants indicated that they did not receive any information regarding pain relief pre-or postoperatively.…”
Section: Activitymentioning
confidence: 99%